Astragalus membranaceus Additive Improves Serum Biochemical Parameters and Reproductive Performance in Postpartum Dairy Cows - Huang, Yinghao; Yan, Qi; Jiang, Maocheng; Guo, Sheng; Li, Huiwei; Lin, Miao; Zhan, Kang; Zhao, Guoqi; Duan, Jinao (Frontiers in Veterinary Science, 2022)
The purpose of the study was to assess the recovery, immune function, and breeding efficiency of postpartum dairy cows fed Astragalus membranaceus (AM) as a feed additive. The experiment used a completely randomized design. Cows were randomly assigned to two groups: (1) Control group fed total mixed ration (TMR; CON group, n = 15); (2) AM group fed TMR and AM (AM group, n = 15). The AM group was fed 675 g/day. The experimental results showed that compared with the CON group. The breeding interval of the AM group of dairy cows had a tendency to shorten (0.05 < p < 0.1). Plasma viscosity (PV), Plasma fibrinogen (FIB), the red cell aggregation index (TRCAI), Calcitonin (CT), Immunoglobulin M (IgM), and Luteinizing hormone (LH) results of AM group showed a time-treatment interaction (p < 0.05). Furthermore, the result of the study revealed that feeding AM as feed additives to dairy cows during the postpartum period had positive effects on wound recovery, immune function, endocrine regulation, and breeding efficiency.